Perception of private sectarian high school teachers on fair presentation of issues on the performance of Iloilo government officials by AM Radio commentators. - Denopra, Janet
Fairness is a pressing issue in broadcast media particularly in Iloilo where commentators of AM stations are believed to be unfair in tackling the issue on the performance of Iloilo government officials., The researchers considered this study as significant since fairness in radio commentary programs have always been questioned. This study was intended to ascertain whether AM radio commentators in Iloilo City present the issue on the performance of Iloilo government officials fairly. To achieve the said purpose, the researchers chose the private sectarian high school teachers of Iloilo City as their respondents. Only fifty percent (or 121) of the entire population of private sectarian high school teachers were chosen as respondents of this study. Thirteen private sectarian high schools in Iloilo City participated in the study (with the non-participation of Assumption). The study made use of questionnaire in order to obtain the necessary information. The first part asked questions pertaining to the listener-ship of the respondents to AM radio commentaries. Out of 121 respondents, 94 listened to AM radio commentaries, 21 said they would listen "sometimes" and 6 never listened at all. The second part of the questionnaire evaluated the perception of the respondents regarding the presentation of the issue on the performance of Iloilo government officials by AM radio commentators. As to the number of sides the commentators presented, 62 of the respondents confirmed that "many" (3) sides of an issue were presented. There were 23 who answered "all" (4 or more), 21 answered "few" (2) and 4 said "only 1 side" of an issue was presented. According to 67 of the respondents, the allotment of time to air each side was almost equal, that is 25-29 minutes vs. 30 minutes. There were 24 who professes the distribution of time was "unequal" (20-24 vs. 30 minutes), 13 said it was "definitely equal" (30 vs. 30 minutes). During elections, political candidates were given equal time on air. This was agreed upon by 56 respondents. However, 34 insisted that commentators did not give equal time. A majority (65) of the respondents denied any use of profane language during the commentary programs. Twenty-four believed otherwise while 9 remained uncertain. Fifty-seven of the respondents replied that the presentation of the issue on the performance of Iloilo government officials by AM radio commentators was fair. This confirms the researchers' conclusion (as based from the FCC's standard of fairness) that indeed AM radio commentators were fair in presenting issues on the performance of Iloilo government officials.